Human Megasatellite DNA RS447: Copy-Number Polymorphisms and Interspecies Conservation - Gondo, Yoichi; Okada, Takeya; Matsuyama, Noriko; Saitoh, Yasushi; Yanagisawa, Yoshiko; Ikeda, Joh-E (Genomics (San Diego, Calif.), 1998)
We previously isolated a novel 4.7-kb RS447 sequence, which tandemly repeated approximately 50–70 copies and resided on human chromosome 4p15 (M. Kogiet al.,1997, Genomics 42: 278–283). Another tandem array (or arrays) of several RS447 copies was hereby identified on the distal part of chromosome 8p. To analyze copy-number polymorphisms of the RS447 repeats, genomic DNA samples of eight nonkindred Japanese were subjected to pulsed-field gel electrophoresis. The copy numbers of the RS447 tandem arrays on 4p15 varied drastically from allele to allele and ranged from approximately 34 to 94 copies. All eight Japanese subjects were apparently heterozygous for the RS447 copy number, and 12 copy-number-different alleles have been at least clearly distinguished. The RS447 tandem repeats were thus found to be hypervariable and highly polymorphic in a human population. The RS447 sequences, however, do not appear to be either “selfish” or “junk” DNA. The unit size and sequence of RS447 were found to be very similar between members in the human genome. The unit size of 4746 bp comprises a putative open reading frame of 1590 bp. The RS447 sequence was well conserved in all the tested mammalian species. The head-to-tail tandem repetitive structure in the RS447 homologs was also confirmed in those species. The RS447 sequence is, therefore, considered to consist of a new class of tandemly repeated satellite DNA elements in the mammalian genome, which may thus be called “megasatellite DNA.”